The Effect of Problem-based Learning on 7th-grade Students’ Environmental Knowledge, Attitudes, and Reflective Thinking Skills in Environmental Education - Evrim Ural; Guzide Dadli (Journal of Education in Science, Environment and Health)
The study aimed to investigate the effect of authentic problem-based learning (PBL) activities in the unit of “Human and Environment” on 7th graders’ environmental information, their reflective thinking skills and their environmental attitudes. The sample of the study consisted of 53 7th grade students from two different classes attending Science and Technology Course at a government school in Turkey. One of the groups was attended as control group the other one was attended as experimental groups. Reflective Thinking Skills Scale, Environmental Knowledge Test, and Environmental Attitude Scale were used as data collection tools. The research design of the study was quasi experimental pre-test post-test control group design. The experimental group was taught by PBL and the control group was taught by didactic teaching method. The results of the study displayed that PBL had significant effect on 7th graders’ environmental knowledge; environmental attitudes but it had no significant effect on students’ reflective thinking skills.